Can Instagram and TikTok Improve Student’s Knowledge about MonkeyPox in Digital Health Communication? - Yeheskiel Benaya Entaren; Asep Rahman; Odi Roni Pinontoan (Asia Pacific Journal of Interdisciplinary Studies, 2025)
This study aims to provide an overview of student’s knowledge levels regarding Monkeypox before and after receiving education through social media platforms Instagram and TikTok. Monkeypox is an infectious disease of global concern, making comprehensive understanding crucial, particularly among adolescents who actively use social media as a primary source of information. This research employs a quantitative descriptive design with a survey approach. The sample consists of 120 10th grade students from SMA Negeri 9 BINSUS Manado who participated in Monkeypox education through Instagram and TikTok. Data were collected using pre-test and post-test questionnaires to assess students' knowledge levels before and after the intervention. The results of the knowledge distribution analysis indicate a significant increase in students' knowledge after receiving education via social media. Most students who initially had a low level of knowledge experienced an improvement after being exposed to interactive and visually engaging content on Instagram and TikTok. This improvement highlights the role of social media as an effective health education tool in disseminating information about infectious diseases such as Monkeypox. The findings of this study affirm that social media can serve as a strategic digital health communication platform to enhance adolescent awareness of health issues. Given the accessibility and engaging nature of social media, health information can be disseminated more widely and effectively. Further research is recommended to explore the effectiveness of different content types and social media platforms in supporting digital-based health education initiative.